Heritage retention and bean intake correlates to dietary fiber intakes in Hispanic mothers— Qué Sabrosa Vida - Smith, Whitney Elizabeth; Day, R. Sue; Brown, Lora Beth (Journal of the American Dietetic Association, 2005)
To determine the correlation between fruit/vegetable and bean stage of change and heritage retention with fiber intake in Hispanic mothers. Cross-sectional study design used baseline survey data from the Qué Sabrosa Vida nutrition intervention developed by the University of Texas School of Public Health, Human Nutrition Center (Houston, TX). Participants were recruited and data gathered from telephone surveys using random digit dial methodology ensuring proportional representation of demographic subgroups. Hispanic mothers (N=293) responded to the baseline survey in El Paso, TX. Using SPSS version 11.0 (SPSS Inc, Chicago, IL), descriptive statistics, χ 2, correlations, and analyses of variance were used to determine the relationship of variables to fiber intake. Potential confounding variables included were grain stage of change, age, education level, and marital status. Mean fiber intake for mothers was 21.9 g/day and mean age was 35.8 years. χ 2 of fruit/vegetable stage was P=.784. χ 2 of bean stage, heritage retention score, age, and education to fiber intake were significant, P=.008, P=.004, P=.005, and P=.001, respectively. Bean stage, heritage retention score, age, and education level were significantly correlated. One-way analysis of variance of bean stage, heritage retention score, age, and education level by fiber intake were significant, P=.006, P=.001, P=.004, and P=.002, respectively. Older Hispanic mothers in the action/maintenance bean stage with strong heritage retention score had greater fiber intakes than younger mothers in pre-action bean stage with weak heritage retention score. As education level increased fiber intake decreased. Encouragement of bean consumption and heritage retention may increase fiber intake in this Hispanic mother population.